Cell Therapy: The Final Frontier for Treatment of Neurological Diseases. (17th December 2012) - Dutta, Susmita; Singh, Gurbind; Sreejith, Sailaja; Mamidi, Murali Krishna; Husin, Juani Mazmin; Datta, Indrani; Pal, Rajarshi; Das, Anjan Kumar
Summary Neurodegenerative diseases are devastating because they cause increasing loss of cognitive and physical functions and affect an estimated 1 billion individuals worldwide. Unfortunately, no drugs are currently available to halt their progression, except a few that are largely inadequate. This mandates the search of new treatments for these progressively degenerative diseases. Neural stem cells (NSCs) have been successfully isolated, propagated, and characterized from the adult brains of mammals, including humans. The confirmation that neurogenesis occurs in the adult brain via NSCs opens up fresh avenues for treating neurological problems. The proof‐of‐concept studies demonstrating the neural differentiation capacity of stem cells both in vitro and in vivo have raised widespread enthusiasm toward cell‐based interventions. It is anticipated that cell‐based neurogenic drugs may reverse or compensate for deficits associated with neurological diseases. The increasing interest of the private sector in using human stem cells in therapeutics is evidenced by launching of several collaborative clinical research activities between Pharma giants and research institutions or small start‐up companies. In this review, we discuss the major developments that have taken place in this field to position stem cells as a prospective candidate drug for the treatment of neurological disorders.